COVID-19 and Cancer Therapy: Interrelationships and Management of Cancer Cases in the Era of COVID-19 - Simon N. Mbugua; Lydia W. Njenga; Ruth A. Odhiambo; Shem O. Wandiga; Martin O. Onani (Journal of Chemistry)
The COVID-19 global epidemic poses this generation’s biggest worldwide public health challenge probably since the 1918 influenza epidemic. Recent reports on two new variants have triggered a dramatic upsurge in research to understand the pandemic, primarily focussing on the virology, triggers, clinical characteristics, and diagnostic tests including the prevention and management of the novel coronavirus. Whilst such studies are important in managing the present medical emergency, there is a need for further work to include interdependencies between the epidemic and other illnesses. This will help in developing effective approaches to treat and manage associated diseases in both the short and the long term. In this regard, people living with cancer are a subgroup that is highly vulnerable to respiratory infections and acute pneumonitis similar to the one caused by the COVID-19 virus. This is because the state of their immunity is compromised due to malignancy and the adverse effects of anticancer treatments. With annual cancer projections rising globally and an estimated 70 percent of all cancer-related deaths occurring in low- and middle-income countries, the patient population with impaired immune systems that could be adversely impacted by COVID-19 is only anticipated to rise. In this review, we delve into the challenges and health risks facing cancer patients and cancer treatment in the COVID-19 context, with suggestions into viable measures which can be taken to minimize exposure to the risk of contracting COVID-19 for this vulnerable subgroup. New mutations and the prospects offered by vaccines development and how they relate to this class of patients are also discussed.